Analyzing the business advisory role in enhancing the growth of SME's in Malaysia: a preliminary study of the east coast / Mohd Zainuri Muhammad, Yeop Hussin Bidin and Julaina Baistaman - Muhammad, Mohd Zainuri; Bidin, Yeop Hussin; Baistaman, Julaina (2011)
As Malaysia steers itself to the rapid pace of the global economy, so too is the government reliance of SME's as an important force in sustaining national economic growth. The business advisory roles were initially identified as an important channel to be the business incubation centre with the aim of facilitating advice and assistance to entrepreneurs in the small medium industry. Therefore, this study is trying to determine the extent of Business Advisory role in enhancing the growth SME's in Malaysia especially pertaining to the East Coast Region. The data was collected from 47 existing clients of the SME bank branch in Kelantan, Pahang and Terengganu. Analysis to establish relationship between variables had shown that customer management, benchmarking were significantly positive in relation the SME's organization to performance while the role of business advisory in strategy development is not considered the contribution for SME's. The finding also showed that, customer management is highly correlated among variables in this study which indicates SME's believed the important in managing the customers followed by benchmarking.